Information and mathematical modelling in construction in the development of building products for fire detection in a neighboring building - A. A. Lazarev; S. V. Fedosov; V. G. Kotlov; D. E. Tsvetkov; A. Yu. Komlev (Vestnik MGSU)
Introduction. The analysis of scientific literature and patent documentation has shown the presence of a significant number of algorithms and solutions for modelling individual elements, structures, partitions, floors and walls to ensure fire safety of buildings and structures. The main approaches to solving these problems are related to the theory of heat transfer. At the same time, there is practically no development of algorithms for the use of building products to detect a fire in a neighboring building.Materials and methods. Information technologies are used to solve practical problems of algorithmization in construction.Results. The algorithm developed by the authors for the application of building products involves checking two specific conditions. This is done to avoid false triggering of the fire detector due to sunlight and to establish the fact that the product is serviceable after a fire. The practical significance of the conducted research also lies in the results of the numerical experiment. Taking into account the basics of theory and mathematical modelling of mechanical and thermal processes, the case of uniform initial temperature distribution in a steel disc of a building product for fire detection in an adjacent building was considered.Conclusions. The obtained equations make it possible to determine the temperature fields in the steel disk of a thermosensitive element of a building product for fire detection in a neighboring building in the process of heat transfer to the medium of various gases. The conducted research also made it possible to perform a comparative analysis of the dynamics of changes in temperature fields depending on the Fourier number of the thermosensitive element of the construction product under consideration for different media separately: argon, krypton, xenon, carbon dioxide, as well as in a vacuum of 10–5 mm Hg.